2019
DOI: 10.1089/aid.2018.0242
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to Donate Hair Samples for Research Among People Living with HIV/AIDS Attending a Tertiary Health Facility in Ibadan, Nigeria

Abstract: The use of hair samples in biomedical research is a rapidly growing field. High acceptability rates for hair collection have been demonstrated in multiple settings. Each setting may have unique issues and, to our knowledge, no previous study has assessed the acceptability of hair sampling for HIV-related research in Nigeria. This study aimed to assess the willingness to donate hair for research among people living with HIV (PLWH). A cross-sectional study was conducted among 381 PLWH in a tertiary institution i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
(50 reference statements)
0
3
0
Order By: Relevance
“…Short-term and long-term EFV exposure were determined in DBS and hair samples, respectively. Moreover, hair sample collection was highly successful in this Nigerian cohort (100% acceptability) despite beliefs in this setting that a person's hair can be used for ritual purposes [ 20 ]. We showed significant association between EFV metabolism in CYP2B6 and concentrations of the drug in both plasma and hair.…”
Section: Discussionmentioning
confidence: 99%
“…Short-term and long-term EFV exposure were determined in DBS and hair samples, respectively. Moreover, hair sample collection was highly successful in this Nigerian cohort (100% acceptability) despite beliefs in this setting that a person's hair can be used for ritual purposes [ 20 ]. We showed significant association between EFV metabolism in CYP2B6 and concentrations of the drug in both plasma and hair.…”
Section: Discussionmentioning
confidence: 99%
“…30,46,47 We had planned to directly measure antiretroviral drug levels in hair, 48 but less than a quarter of participants provided hair sample, likely linked to Nigerian men's preference for short hair plus fears among Nigerians that hair may be used for rituals. 49 Antiretroviral drug levels in dried blood spots will be used to objectively measure adherence in the next phase of our study. Finally, it remains to be seen whether already stretched health systems will be able to provide resources such as mobile phones that the study purchased for 40 percent of participants.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, about 77% of immigrant population in the USA reported a willingness to donate tissue for research purposes [30]. The same level of willingness to donate tissue for research has been reported was in countries such as Canada, Sweden, Nigeria, and Jordan [31][32][33][34]. In Poland, the willingness to donate tissue for research has been to vary according to tissue type ranging from 74% for urine samples to 20% for post-mortem brain fragments [35].…”
Section: Discussionmentioning
confidence: 85%